Polysaccharides-Rich Extract From Fruiting Body Of Mushroom (Pleurotus Pulmonarius) As A Potential Source Of Prebiotic - Leow, Kim Teck (2020)
Prebiotic is capable to modulate the composition of beneficial gut microbiota for disease prevention and immunomodulation of the host. Prebiotic potential of polysaccharides-rich extract (PRE) from Pleurotus pulmonarius is unknown. Research was carried out to determine the physicochemical properties and prebiotic characteristics of PRE, and to assess the synbiotic relationship of PRE with Lactobacillus acidophilus FTDC3871 (La3871) and PRE with Lactobacillus bulgaricus FTDC1511 (Lb1511).